Implementasi Competitive Strength, Competitive Area, Competitive Result dalam Peningkatan Daya Saing dan Pemasaran Jasa Pendidikan Islam - Bambang Wiratmuko; Prim Masrokan; Agus Eko Sujianto (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2023)
His research aims to describe competitive strengths, competitive areas, and Competitive results in improving the competitiveness and marketing of Islamic education services. The urgency of this research is that a deep understanding and implementation of appropriate strategies in competitive strength, competitive area, and Competitive Result can optimize the competitiveness and marketing of Islamic education services. This type of research is categorized as library research using a descriptive-qualitative approach to examine competitive strength, competitive area, and Competitive Result as strategies to optimize the competitiveness and marketing of Islamic education services. Competitive strength includes various factors that play a role in influencing competitiveness. One important aspect is the quality of education. Educational institutions that provide a relevant curriculum, have qualified teachers, and use effective teaching methods have an advantage in providing an optimal learning experience for students. Competitive areas include specific market segments or the overall market that an educational institution targets. It is important to accurately identify and understand these competitive areas in order to effectively direct the marketing and development strategies of educational institutions. Competitive Results in the context of Islamic educational institutions include the achievements and outcomes that are sought to improve their competitiveness. The strategic objectives of competitive outcomes are to achieve competitive advantage, drive growth, and ensure long-term success for the institution..